Culture Malay community value profane on modern Malaysian Islamic Art Exhibition/ Wan Samiati Andriana WMD ... [et al.] - WMD, Wan Samiati Andriana; Mokhtar, Mumtaz; Arzain, Noriza; M.Hum, Yulriawan Dafri (Universiti Teknologi MARA, Perak, 2023)
Art and culture are two entities that are closely related and are suspended from each other. The arts have become an identity and practice essential to Malaysia’s cultural society, which is a multiracial nation. With the diversity of the art practices of multi-ethnic societies in the country, the identity of multicultural Malaysia has become more highlighted and recognizable. The objective of this paper is to gather visual artwork on Culture values found in the Islamic exhibition from 1957 to 1999. The artworks have been put into consideration and recorded accordingly, such as the artwork’s title, dimension or size of the artwork, media, and techniques used in producing the artwork. The researcher followed the integrative approach and applied the technique of the descriptive quantitative approach. The information gathered through data collection inclusive of three major issues, the concept, the national policies, and the events or exhibitions gathered from various sources, including academic books, journals, proceedings as well as exhibition catalogues cum books of painting, retrospectives, biographies, competition booklets, and website. The important events on Islamic art were also gathered through the articles presented at seminars and symposiums as well as newspaper cuttings and magazines. It is hoped that through visual arts, generations of Malaysians will be literate in culture, have high aesthetic values, critical, creative, imaginative, innovative, and inventive, as well as explore thought explorations, and design in a wide range of visual arts to allow the development of ideas and self-expression.